Personal and Social Resources at Work: Reciprocal Relations Between Crafting for Social Job Resources, Social Support at Work and Psychological Capital - Kerksieck, Philipp; Bauer, Georg F.; Brauchli, Rebecca (Frontiers in Psychology, 2019)
Abstract The availability and development of social and personal resources are substantial components of a positive work experience. This study aims to further inquire the reciprocal relations between the personal resource of psychological capital (PsyCap; hope, self-efficacy, resilience, and optimism) and the social job resource of social support, as proposed in the job demands-resources theory. There, job crafting is defined as a catalysator to the interplay of social support and PsyCap and is therefore added to this study. Moreover, we test the enabling hypothesis of social support in the context of work. We contribute to the field, as this research a) examines propositions of a core theory, b) adds and extends relevant hypotheses from health psychology into occupational psychology, and c) aims to replicate findings. To capture the dynamic nature of the selected, relevant relationships of the job demands-resources theory, we used a three-wave, three-month panel design to study 995 employees who were working in a broad range of economic sectors and occupations. Structural equation modeling was used to test hypotheses. Results showed, that social support at work positively influenced the development of PsyCap, supporting and extending the enabling hypothesis of self-efficacy. Counterintuitively, PsyCap and crafting for social job resources were negatively related, indicating a) that the reliance on personal resources might reduce the necessity to generate social resources, and b) that crafting is a strategy that consumes personal resources. Previously observed gain cycles were not replicable.